Determination of structural homogeneity of synthetic diamonds from analysis of Kikuchi lines intensity distribution - Fodchuk, I.; Balovsyak, S.; Borcha, M.; Garabazhiv, Ya.; Tkach, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
It has been suggested the technique based on analysis of geometry and
intensity distribution profiles in Kikuchi patterns obtained due to electron backscattering
diffraction for defining structural imperfection of diamond crystals. To determine the
geometry parameters in Kikuchi patterns with the maximal precision, the special
software was developed. It has been shown that application of electron diffraction
(Kikuchi method) allows to obtain information about degree of perfection and
homogeneity of real structure for diamond crystals synthesized with various methods.